Emblica extract prevents cisplatin-induced apoptosis in dermal papilla fibroblasts - Sudjit Luanpitpong; Varisa Pongrakhananon; Ubonthip Nimmannit; Pithi Chanvorachote (Songklanakarin Journal of Science and Technology (SJST), 2008)
Cisplatin is a widely prescribed anticancer agent that causes hair loss in patients. Since the dermal papilla (DP) fibroblasts are known to be a key mediator in controlling hair growth and loss, understanding the effect and underlying mechanism of cisplatin on these cells may lead to new strategy for hair loss protection in chemotherapy patients. Less is known regarding the effect of cisplatin on DP fibroblasts. We thus treated DP cells with cisplatin (0-250 mmol/L) and found that cisplatin induced DP cell death in a concentration-dependent manner. Our results showed that the mode of cisplatin-induced DP cell death was mainly through apoptosis mechanism. Our results also indicated that the intracellular reactive oxygen species (ROS) induction caused by cisplatin treatment was associated with DP cell apoptosis and cisplatin-induced apoptosiscould be attenuated by addition of antioxidant N-acetylcysteine (1 mmol/L) and glutathione (5 mmol/L). Moreover, subtoxicconcentrations (0-500 mg/mL) of Phyllanthus emblica Linn (emblica) extracts, a known natural antioxidant, showed a strong inhibition effect on cisplatin-induced intracellular ROS induction and subsequently protected DP cells from cisplatin-induced apoptosis.